Differential responses toward conditioned and unconditioned stimuli, but decreased hypothalamic-pituitary-adrenal axis responsiveness in neonatal hippocampal lesioned monkeys. (December 2022) - McKeon, Emma; Torres, Jennifer; Kazama, Andrew M.; Bachevalier, Jocelyne; Raper, Jessica
Abstract: The hippocampus is important for long-term memory storage, but also plays a role in regulating the hypothalamic-pituitary-adrenal (HPA) axis and emotional behaviors. We previously reported that early hippocampal damage in monkeys result in increased anxious expression and blunted HPA responses to an acute stressor. Here, we further probe their responses toward aversive stimuli (conditioned and unconditioned) and evaluate HPA axis dysfunction. Responses toward social, innate, and learned aversive stimuli, fear potentiated acoustic startle, and pituitary-adrenal function were investigated in 13 adult rhesus monkeys with neonatal hippocampal lesions (Neo-Hibo=6) and controls (Neo-C=7). Neo-Hibo monkeys' responses depend on the type of unconditioned stimulus, with increased anxiety behaviors toward social and learned, but decreased reactivity toward innate stimuli. Neo-C and Neo-Hibo monkeys exhibited similar performance learning conditioned cues and safety signals. Neo-Hibo monkeys were less sensitive to HPA axis stimulation, potentially suggesting adrenal fatigue. Current findings suggest that the hippocampus plays a large role in regulating not only anxiety behaviors, but also the HPA-axis, a neural system crucial to regulate how we respond to the world around us. These data have important clinical significance considering that many developmental neuropsychiatric disorders exhibit altered hippocampal structure and function, emotional and HPA axis dysregulation.